Synthesizing collaborative reflections on classroom observation frameworks and reflecting on the necessity of synthesized frameworks. (December 2022) - Charalambous, Charalambos Y.; Praetorius, Anna-Katharina
Abstract: Researchers use various classroom observation frameworks and instruments to assess teaching quality. This jeopardizes the development of a comprehensive and cumulative understanding of teaching quality. Promoting collaboration between the proponents of different frameworks could help remedy the situation. For this special issue we offered three groups of researchers, each representing a different framework category (content-generic, content-specific, and hybrid), a chance to collaborate, and this paper summarizes and discusses the ideas which emerged. There were significant overlaps between the groups, but also notable differences in how even frameworks in the same category conceptualized, operationalized, and measured teaching quality. These differences have implications for research and practice. They also highlight the need for developing and using frameworks that synthesize across existing teaching-quality work. Using MAIN-Teach as an example, we reflect on the possibilities and limits of such frameworks and outline directions for advancing work on developing such frameworks in the future. Highlights: Comparing frameworks facilitates rich collective discussions on teaching quality. Differences found within and across categories of classroom observation frameworks. Differences matter for research and formative/summative evaluation purposes. Both single and synthesized frameworks are needed and can serve different purposes. Conceptualization warrants notable attention in developing (synthesized) frameworks.